2023
DOI: 10.1021/acs.est.3c00032
|View full text |Cite
|
Sign up to set email alerts
|

Multi- and Transgenerational Developmental Impairments Are Induced by Decabromodiphenyl Ethane (DBDPE) in Zebrafish Larvae

Abstract: A novel brominated flame retardant decabromodiphenyl ethane (DBDPE) has become a ubiquitous emerging pollutant; hence, the knowledge of its long-term toxic effects and underlying mechanism would be critical for further health risk assessment. In the present study, the multi-and transgenerational toxicity of DBDPE was investigated in zebrafish upon a life cycle exposure at environmentally relevant concentrations. The significantly increased malformation rate and declined survival rate specifically occurred in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 68 publications
(111 reference statements)
6
13
0
Order By: Relevance
“…Glu is known as a major excitatory neurotransmitter, while GABA usually acts as an inhibitory neurotransmitter . Previous studies have mentioned that PBDEs, such as PBDE-47 and PBDE-99, have the ability to alter the function of GABA receptors and caused hyperactivity in mice. , A recent study reported elevated Glu and GABA levels followed by increased transcription of the Glu receptor and decreased transcription of the GABA receptor in zebrafish larvae exposed to DBDPE at environmentally relevant concentrations, indicating combined action of these neurotransmitters in behavioral control . Similarly, in the current study, we also observed an increase in the mRNA levels of the Glu receptor, ionotropic N -methyl- d -aspartate 3A ( grin 3 a ), and those of GABA type A receptor subunits alpha3 and 6 ( gabra 3 and gabra 6) were decreased in zebrafish larvae ( P < 0.05, Figure C).…”
Section: Results and Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Glu is known as a major excitatory neurotransmitter, while GABA usually acts as an inhibitory neurotransmitter . Previous studies have mentioned that PBDEs, such as PBDE-47 and PBDE-99, have the ability to alter the function of GABA receptors and caused hyperactivity in mice. , A recent study reported elevated Glu and GABA levels followed by increased transcription of the Glu receptor and decreased transcription of the GABA receptor in zebrafish larvae exposed to DBDPE at environmentally relevant concentrations, indicating combined action of these neurotransmitters in behavioral control . Similarly, in the current study, we also observed an increase in the mRNA levels of the Glu receptor, ionotropic N -methyl- d -aspartate 3A ( grin 3 a ), and those of GABA type A receptor subunits alpha3 and 6 ( gabra 3 and gabra 6) were decreased in zebrafish larvae ( P < 0.05, Figure C).…”
Section: Results and Discussionsupporting
confidence: 88%
“…Taken together, the untargeted metabolomics results in this study figured out obviously different metabolomic profiles upon DBDPE exposure, which may affect the pathways involving glycolipid metabolism, oxidative phosphorylation and oxidative stress as further validated. Similar effects have been widely reported in previous studies of traditional BFRs (e.g., BDE-47, BDE-100, and BDE-209), most of which suggested a potential mechanism related with mitochondrial injury. ,, Our recent study using multiomics also provided important clues for mitochondrial dysfunctions in DBDPE-induced adverse effects in zebrafish larvae . Therefore, we next would like to verify the damage on the mitochondrial function and its role in DBDPE-induced adverse effects.…”
Section: Results and Discussionsupporting
confidence: 81%
See 3 more Smart Citations